Parenting Support Communication Model Development Using Whatsapp Messenger in TK Islam Mutiara Hikmah Dan Lalita Kita Bintaro - Lilik Sumarni; Annisa Putri Larasati; Daniel Handoko (Asian Social Work Journal, 2019)
Parenting for early childhood should be prioritized due to the importance of both physical and psychological aspects of children’s growth and development. A parenting model accompanied by parents, teachers and also psychological experts will result the balance oh physical and psychological health of the children. The development of social media like WhatsApp Messenger which has not been used optimally for parenting support socialization could be mentioned as an unfortunate chance. Due to that matter, the purpose of this research, thus: to describe the existing communication flow between parents and the school of TK Islam Mutiara Hikmah dan TK Lalita Kita Bintaro, to describe the result of parenting support model development in the teachers’ and parents’ behavior, and to find supporting and challenging factors to the communication development of the parenting model support that uses the WhatsApp Messenger. Methodology used in this research is descriptive methodology by the qualitative approach. Furthermore, the informants are invited by purposive and accidental methods. The informants consisted of two educators at TK Mutiara Hikmah, two psychologists from both schools, two educators at TK Lalita Kita Bintaro, eight students’ guardians from TK Mutiara Hikmah and nine students’ guardians from TK Lalita kita Bintaro. Data collection is conducted by doing in- depth interviews, documentations, and observation. The data analysis technique is conducted by using qualitative analytical method and descriptive method periodically since the beginning of data collection to the end of the research. To create the meaning of concluded data, researchers did the data analysis and the interpretation. The validity of data is tested by implementing source triangulation. Research output is to develop the communication model of parenting support by using WhatsApp Messenger. Theoretical basis used in this research is Osgood and Schramm’s Circular Communication Model. This model of communication is laid on the understanding that communication is conducted by two sides. Osgood explains that communication exists circularly rather than in linear way. The research is done for 6 months from January 25–July 25 2018. The results show: 1. The description of communication flow between teachers and parents has not been carried out in significant way since there are many parents working. Thus, the researchers tried to develop the communication model for parenting support by using WhatsApp Messenger to ease the more interactive communication for working parents. Furthermore, the use of social media could also ease the delivery of parenting support materials such as, curriculums, school’s subjects, and the announcements so that more dynamical communications with feedback can exist. 2. The result of parenting support model development is the coordination of the parenting support program can be done easier and optimally for those who already have the WhatsApp Messenger account. The delivery of materials and discussions via WhatsApp Messenger gives solution for parenting support problem. Significant results are as follow: a. Parents got helped by sharing activities via WhatsApp Messenger, b. Those materials shared via WhatsApp made children more independent and easier to control the psychological development, c. Children get braver at school and hyperactive children get calmer, d. Facilitating the problem solving process, e. Changing of children’s behavior such as, communication skills, concern feelings, and getting more method of learning and playing based on the ages, f. Raising concern for parents about all aspects of children’s growth and development, g. Giving more knowledge of parenting to parents by visualizing it through videos and variative tutorials. Supporting and challenging factors to the development of communication model via WhatsApp Messenger are as follow: internet connection service, financial problem of parents to provide the facilities and phycologists, schools’ poor facilities and infrastructures, and poor parents’ role since they are working are the challenging factors. While supporting factors are parents’ concern, internet connection, dynamic discussion between parents and teachers so that parents could easily implement the materials at home, and facilities provided by school, teachers’ concerns to children’s psychological development. Communication flow between parents and teachers has not been conducted optimally even though WhatsApp Messenger was already used by them, this model is positively reacted by the school and parents, and also, the benefits are considered directly. Furthermore, significant factors for the success of this model is human resources, facilities and infrastructure, and financial problems.